The Influence Oh Human Relations And Work Commitment On The Work Dicipline Of Civil Servants At The Tasikmalaya District Transportation, Comunication And Informatics Office - Karima, Salsabila; Karmila, Mila; Patimah, Titin (Universitas Dehasen Bengkulu, 2024)
This study aims to determine the effect of Human Relations and Work Commitment on Civil Servant Work Discipline at the Tasikmalaya Regency Transportation, Communication and Informatics Office (DISHUBKOMINFO). This research uses quantitative methods. The population in this study were 81 civil servants of the Transportation, Communication and Information Technology Office (DISHUBKOMINFO) of Tasikmalaya Regency. The sampling technique in this study used multiple linear regression analysis using SPSS version 23. The results of this study indicate that Human Relations and Work Commitment simultaneously have a significant effect on the work discipline of civil servants at the Transportation, Communication and Information Technology Office (DISHUBKOMINFO) of Tasikmalaya Regency. Human Relations partially has a significant effect on the work discipline of civil servants at the Office of Transportation, Communication and Information Technology (DISHUBKOMINFO) Tasikmalaya Regency. Work Commitment partially has a significant effect on the work discipline of civil servants at the Office of Transportation Communication and Informatics (DISHUBKOMINFO) Tasikmalaya Regency.